2006
DOI: 10.1007/s00216-006-0937-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of Raman spectroscopy to provide an estimation of the gross biochemistry associated with urological pathologies

Abstract: Near-infrared Raman spectroscopy, an optical technique that is able to interrogate biological tissues, has been used to study bladder and prostate tissues, with the objective being to provide a first approximation of gross biochemical changes associated with the process of carcinogenesis. Prostate samples for this study were obtained by taking a chip at TURP, and bladder samples from a biopsy taken at TURBT and TURP, following ethical approval. Spectra were taken from purchased biochemical constituents and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
102
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 15 publications
13
102
0
Order By: Relevance
“…Our approach was to select only one Raman constituent to represent those in situ components that were chemically similar and with high collinearity. Similarly, Stone et al demonstrated that including both amino acids and the proteins containing them in a linear model skewed the fit coefficients [16]. Our experience is that minimizing the number of protein components resulted in the most consistent fit coefficients.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our approach was to select only one Raman constituent to represent those in situ components that were chemically similar and with high collinearity. Similarly, Stone et al demonstrated that including both amino acids and the proteins containing them in a linear model skewed the fit coefficients [16]. Our experience is that minimizing the number of protein components resulted in the most consistent fit coefficients.…”
Section: Discussionmentioning
confidence: 53%
“…The building blocks of our model are Raman active components extracted from skin in situ. Previous biophysical models used model components either measured directly from synthetic/purified chemicals [9,[15][16][17][18], or extracted from tissue sections in situ [19][20][21]. The advantage of using synthetic/purified chemicals as model components is that they can be easily measured without the need for Raman micro-imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy (RS) is based on molecular inelastic scattering of light [6]: when photons interact with a molecule, the transmission of their energy raises the molecule's vibrational state. When the molecule returns to its background level, a photon is emitted at a different wavelength from the incident light.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the use of a wide range of substrates including calcium uoride, [8][9][10] aluminium, 11,12 quartz 13-15 and 3D collagen gels. 16 However, substrates that produce low background signals for NIR sources are oen expensive, and are available in different levels of purity/lm thicknesses, which can produce variable results with Raman spectroscopy.…”
Section: Sample Substratesmentioning
confidence: 99%